Place of Physcial Environment in Personality Education According to Muhammad lqbal - GÜREL, RAMAZAN (CUMHURIYET UNIV, FAC THEOLOGY, 2017)
When we look at the research done on the history of education, it is possible to come across different ideas about personality-education relation, approaches and theories. Human feelings, thoughts, behaviours, material structure and personality characteristics that are evolving making it necessary to handle him in multi-dimensions. As a result of this situation both in Islamic geography and in the West, many thinkers elaborate the affecting factors on personality development and education, they evaluate the physcial environment and the conditions that change depending on it as an active element influencing personality education. In this our study, we try to put out the ideas that point to the place of physcial environment in personality education of Muhammad Iqbal who has a distinct place in the tradition of Islamic thought with unique ideas about man. In this context, the starting points of our research will be determination the conceptual framework of the personality word and to recognize the physcial environment that Iqbal brings to the agenda in personality education and pointing to the move of the school and the teacher in the personality education process instead of Ikbal's views in connection with the physical environment and to determine the role give place by Iqbal in the physcial environment in terms of its impact on the development of human personality will be the starting points of our research.
Keywords: Muhammad Iqbal; Iqbal; Personality; God-man; Education; Physcial Environment; School; Teacher